(untitled) (Bangladesh Journal of Botany, 2023)
Effects of integrated nutrient management (INM) approach on the growth, yield, and quality of sweet orange [Citrus sinensis (L.) Osbeck] cv. Phule Mosambi was investigated. Eleven treatments were imposed in Complete Randomized Design (CRD) for two seasons (2019 and 2020) and among the treatments, T11 [50% RDN + 20kg FYM/tree + 25% N from Castor Cake + 10ml Bio NPK Consortium + Micronutrient foliar spray (1% Grade IV)] recorded the maximum incremental plant height (35.28 cm), plant spread N-S (45.73 cm), plant spread E-W (45.32 cm) and canopy volume (0.061m3). Similarly treatment T11 significantly increased several yield parameters viz., the maximum fruit length (8.11cm), fruit diameter (7.96 cm), fruit weight (241.91 g), fruit volume (251.17 cc), no. of fruits per tree (255.17), yield (61.81 kg per tree and 17.18 t/ha) in pooled data. Amid quality traits, T11 stood significantly superior with respect to total sugar (6.99 %) content; it also showed higher sugar: acid ratio (14.27), ascorbic acid content (40.11 mg/100 ml pulp). Hence this particular treatment can be adopted preferably in sweet orange cultivation at middle Gujarat (India). Bangladesh J. Bot. 52(2): 345-355, 2023 (June)